2001
DOI: 10.1146/annurev.micro.55.1.485
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-Oxidizing Bacteria: A Model for Molecular Microbial Ecology

Abstract: The eutrophication of many ecosystems in recent decades has led to an increased interest in the ecology of nitrogen transformation. Chemolitho-autotrophic ammonia-oxidizing bacteria are responsible for the rate-limiting step of nitrification in a wide variety of environments, making them important in the global cycling of nitrogen. These organisms are unique in their ability to use the conversion of ammonia to nitrite as their sole energy source. Because of the importance of this functional group of bacteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
745
5
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,151 publications
(795 citation statements)
references
References 225 publications
(316 reference statements)
32
745
5
13
Order By: Relevance
“…2), with all of these Nitrosomonas-like sequences clustering within the N. communis lineage defined by Purkhold et al [5]. These results are consistent with other studies that have shown the dominance of Nitrosospira AOB in terrestrial environments [4,10,18,39,40]. If we examine the proportional occurrence or abundance of Nitrosomonas-like AOB versus Nitrosospira-like AOB in each clone library, we find that nitrosomonads were particularly abundant in the desert soils (MD2, MD3, MD5) where they represented >75% of the sequences in these clone libraries (Fig.…”
Section: Composition Of the Soil Aob Communitiessupporting
confidence: 88%
See 4 more Smart Citations
“…2), with all of these Nitrosomonas-like sequences clustering within the N. communis lineage defined by Purkhold et al [5]. These results are consistent with other studies that have shown the dominance of Nitrosospira AOB in terrestrial environments [4,10,18,39,40]. If we examine the proportional occurrence or abundance of Nitrosomonas-like AOB versus Nitrosospira-like AOB in each clone library, we find that nitrosomonads were particularly abundant in the desert soils (MD2, MD3, MD5) where they represented >75% of the sequences in these clone libraries (Fig.…”
Section: Composition Of the Soil Aob Communitiessupporting
confidence: 88%
“…The abundance of nitrosomonads in desert soils may also be related to soil salinity (which was not measured but which is often higher in desert than in non-desert soils), given that nitrosomads are often halophilic [41]. Although it has been hypothesized that nitrosomonads are likely to become relatively more abundant in soils with high N availability [10,42], our results do not support this hypothesis; we found no significant correlations between the proportional representation of nitrosomonads in the libraries and any of the measured soil and site parameters listed in Table 2 (ρ<0.2, P>0.4 in all cases), including those estimates of soil N availability (extractable NH 4 + concentrations, total dissolved inorganic N concentrations, and net N mineralization rates). However, it is important to note that nearly all of our sites are nonagricultural and have not received high fertilizer inputs so the N availability levels in our soils may be far lower than in soils analyzed in previous studies.…”
Section: Composition Of the Soil Aob Communitiescontrasting
confidence: 86%
See 3 more Smart Citations